Transformasi Kebijakan Publik Pasca Bencana: Studi Kasus Kecamatan Katanga Kota Palu - Nirmala Apsari (Transgenera: Jurnal Sosial, Politik dan Humaniora, 2025)
This research examines the transformation of public policy post-disaster in Katanga District, Palu City, focusing on paradigm shifts and policy adaptation following the 2018 natural disaster. Employing a qualitative approach with case study methodology, the research was conducted through in-depth interviews with 15 key informants and analysis of policy documents from 2018-2024. The findings reveal a fundamental shift from economic development orientation toward a regional resilience-based approach. This transformation was driven by increased collective awareness about disaster mitigation urgency, stakeholder consensus formation, and demands for institutional capacity strengthening. The research findings contribute to the development of public policy adaptation theory in disaster management contexts, while providing a reference framework for formulating responsive policies to disaster dynamics in other regions.